Planning of Cibogo agrotechnopark as an agricultural based edutourism landscape in Cirebon - Ray March Syahadat; Ridwansyah Trisnanda Putra; Ismail Saleh; Rizal Ichsan Syah Putra (Universitas Merdeka Malang, 2022)
The Yayasan Pendidikan Swadaya Gunung Jati (YPSGJ) in Cirebon is a foundation in social education. This foundation has land resources that have not been optimized and plans to develop one of their business unit in the tourism sector. This study aims to plan YPSGJ's land in Cibogo to be developed into a business unit in the tourism sector. This study is a tourism landscape planning study, therefore the method used refers to the Gunn planning stages which consist of setting objectives, research, synthesis conclusions, concepts, and recommendations. Data was collected by interviewing three key informants from YPSGJ, literature study, and observation. Data were analyzed using SWOT analysis to determine the planning concept. The results obtained from the land are planned to be an agriculture-based technopark by combining agro-edutourism activity. There are 7 activity concepts and 13 facility concepts spread over 4 spaces are proposed in this plan. The managerial implications of this study can provide input for YPSGJ to develop its land resources so that the benefits can be felt not only for internal YPSGJ but also for the Cirebon Municipality. The results of this study can also be used as a reference in the field of tourism landscape science as its practical implications.